Long non-coding RNA FGD5-AS1 promotes non-small cell lung cancer cell proliferation through sponging hsa-miR-107 to up-regulate FGFRL1. Issue 1 (24th January 2020) - Fan, Yafeng; Li, Hongxia; Yu, Zhongping; Dong, Wen; Cui, Xiaoyan; Ma, Jinlian; Li, Shengwen
Abstract: Long non-coding RNA (lncRNA) FYVE, RhoGEF and PH domain containing 5 antisense RNA 1 (FGD5-AS1) has been reported as an oncogene in colorectal cancer, promoting its tumorgenesis. The present paper focused on searching the potential function of FGD5-AS1 in non-small cell lung carcinoma (NSCLC). There are connections between the expression of lncRNA FGD5-AS1 and human NSCLC tumor growth and progression. Also, the relationships between FGD5-AS1, hsa-miR-107 and mRNA fibroblast growth factor receptor like 1 (FGFRL1) are going to test their interaction in NSCLC cell lines, which may cause a series of biological behaviors of NSCLC cells. qRT-PCR analysis was conducted to test the expression of RNAs in different situation. CCK-8 experiment and clone formation assay were performed to assess proliferation of NSCLC cells. Also, connection between FGD5-AS1 and hsa-miR-107 were investigated by luciferase reporter assay and RNA pull-down assay. Rescue experiments were performed to verify the modulating relationship between FGD5-AS1, hsa-miR-107 and FGFRL1. High-level expression of FGD5-AS1 was found in NSCLC. FGD5-AS1 may promote the proliferation of NSCLC cells. Also, the combination between hsa-miR-107, FGD5-AS1 and NSCLC have been proved, which means they can play an interaction function in NSCLC cells. Thence, we concluded that lncRNA FGD5-AS1 promotes non-small cell lung cancer cell proliferation through sponging hsa-miR-107 to up-regulate FGFRL1.